Sprawność fizyczna osób w wieku emerytalnym z aglomeracji miejskiej = Fitness of retirement age with urban agglomeration - Ratkowski, Wojciech; Grabowska-Skorb, Paulina; Bzdawski, Maciej; Napierała, Marek; Pezala, Małgorzata; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Ratkowski Wojciech, Grabowska-Skorb Paulina, Bzdawski Maciej, Napierała Marek, Pezala Małgorzata, Zukow Walery. Sprawność fizyczna osób w wieku emerytalnym z aglomeracji miejskiej = Fitness of retirement age with urban agglomeration. Journal of Education, Health and Sport. 2015;5(4):177-194. ISSN 2391-8306. DOI: 10.5281/zenodo.16726 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A177-194 https://pbn.nauka.gov.pl/works/554168 http://dx.doi.org/10.5281/zenodo.16726 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.02.2015. Revised 27.03.2015. Accepted: 05.04.2015. SPRAWNOŚĆ FIZYCZNA OSÓB W WIEKU EMERYTALNYM Z AGLOMERACJI MIEJSKIEJ FITNESS OF RETIREMENT AGE WITH URBAN AGGLOMERATION Wojciech Ratkowski1, Paulina Grabowska-Skorb1, Maciej Bzdawski1, Marek Napierała2, Małgorzata Pezala2, Walery Zukow2 1Akademia Wychowania Fizycznego I Sportu w Gdańsku 2Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: sprawność, ludzie starsi, miasto. Key words: efficiency, the elderly, the city. Streszczenie Celem badań było określenia poziomu sprawności osób w wieku emerytalnym. Do badań zakwalifikowano 109 osób aktywnych fizycznie i grupę kontrolną - 82 osoby nie ćwiczący z Trójmiasta. Do oszacowania sprawności fizycznej użyto testu sprawności fizycznej dla osób starszych The Fullerton Functional Fitness Test składający się z 6 zadań ruchowych. Analiza statystyczna obejmowała analizę opisową i decyzyjną. W skład analizy opisowej weszły prezentacje graficzne i liczbowe otrzymanych wyników. Każda forma uczestnictwa w kulturze fizycznej, każdy rodzaj aktywności fizycznej, poprawa indywidualnej sprawności fizycznej jest pożądana z punktu widzenia konstruowania i realizacji programów prozdrowotnych skierowanych do osób starszych. Niezbędne jest też oszacowanie poziomu sprawności fizycznej osób, do których te programy będą skierowane. Stwarza to potrzebę permanentnego testowania osób w różnych grupach wiekowych i stworzenia bazy danych do opracowania polskich norm sprawności fizycznej osób starszych. Abstract The aim of this study was to determine the level of efficiency of people of retirement age. The study enrolled 109 people who are physically active and the control group - 82 people not practicing with Tri-City. To assess the physical fitness physical fitness test was used for the elderly The Fullerton Functional Fitness Test consisting of 6 motor tasks. Statistical analysis included descriptive analysis and decision-making. The descriptive analysis came pictorial representations and numerical results. Any form of participation in physical culture, any kind of physical activity, improve individual fitness is desirable from the point of view of the design and implementation of health-promoting programs for the elderly. It is also necessary to estimate the fitness level of the persons to whom these programs will be targeted. This creates the need for a permanent testing people in different age groups and create a database for the development of Polish standards of physical fitness of the elderly.